Aortic stiffening and its impact on left atrial volumes and function in patients after successful coarctation repair: a multiparametric cardiovascular magnetic resonance study. Issue 1 (December 2016) - Voges, Inga; Kees, Julian; Jerosch-Herold, Michael; Gottschalk, Hannes; Trentmann, Jens; Hart, Christopher; Gabbert, Dominik; Pardun, Eileen; Pham, Minh; Andrade, Ana; Wegner, Philip; Kristo, Ines; et al.
Abstract Background The increased cardiovascular morbidity of adults with late repair of aortic coarctation (CoA) has been well documented. In contrast, successful CoA repair in early childhood has a generally good prognosis, though adverse vascular and ventricular characteristics may be abnormal, which could increase long-term risk. This study sought to perform a comprehensive analysis of aortic elasticity and left ventricular (LV) function in patients with aortic coarctation (CoA) using cardiovascular magnetic resonance (CMR). In a subgroup of patients, we assessed structure and function of the common carotid arteries to probe for signs of systemic vascular remodeling. Methods Fifty-one patients (median age 17.3 years), 13.9 ± 7.5 years after CoA repair, and 54 controls (median age 19.8 years) underwent CMR. We determined distensibility and pulse wave velocity (PWV) at different aortic locations. In a subgroup, common carotid artery distensibility, PWV, wall thickness and wall area were measured. LV ejection fraction (EF), volumes, and mass were measured from short axis views. Left atrial (LA) volumes and functional parameters (LAEFPassive, LAEFContractile, LAEFReservoir ) were assessed from axial cine images. Results In patients distensibility of the whole thoracic aorta was reduced (p  < 0.05) while PWV was only significantly higher in the aortic arch (p  < 0.01). Distensibility of the descending aorta at the level of the pulmonary arteries and PWV in the descending aorta, both correlated negatively with age at CoA repair. LA volume before atrial contraction and minimal LA volume were higher in patients (p  < 0.05). LAEFPassive and LAEFReservoir were reduced (p  < 0.05), and LAEFReservoir correlated negatively with aortic arch PWV (p  < 0.05). LVEF, volumes and mass were not different from controls. Carotid wall thickness and PWV were higher in patients compared to controls (p  < 0.05). Conclusions Patients after CoA repair have impaired bioelastic properties of the thoracic aorta with impact on LV diastolic function. Reduced descending aortic elasticity is associated with older age at time of CoA repair. The remodeling of the common carotid artery in our sub-studys uggests systemic vessel wall changes.